Educational Transformation In The Midst Of Globalization and Modernization: Issues and Challenges - Lesmana, Gusman; Muharmi, Tetty (INDONESIAN COUNSELING AND PSYCHOLOGY, 2024)
The transformation of education in the era of globalization and modernization has given rise to serious challenges related to access, quality, and relevance, including gaps in access, the commercialization of education, and the penetration of global culture that threatens local values ​​and national identity. This study aims to deeply analyze the challenges of education in the era of globalization and formulate strategies for developing a sustainable education system that is innovative, inclusive, and based on cultural preservation. This study uses a qualitative literature review method with a descriptive-analytical approach. The research subjects were various literature sources, including books, journal articles, and policy documents related to global and local education issues. Data were collected through desk review techniques and analyzed using content analysis methods to identify key themes and strategic solutions. The results indicate that educational transformation requires technology integration, teacher competency enhancement, character building, and the protection of local values ​​amidst the currents of globalization. The conclusions of this study emphasize that the development of an education system must prioritize sustainable innovation, equitable access, cultural preservation, and resilience to global disruption. The implications of this research are expected to provide a basis for consideration for the government, education practitioners, and policymakers in formulating adaptive and sustainable education policies.